A Review on Heavy Metal Toxicity in Livestock: Current Trends and Future Perspectives - Iqbal, Iqra; Ashraf, Asfa (PSM Microbiology, 2022)
The presence of heavy metals in animal feed, whether natural or locally derived, or enhanced by specific manufacturing procedures, has been observed to alter the feed. The bioaccumulation of these heavy metals results in a wide range of toxic effects on various body tissues and organs. Heavy metals boost enzyme activity by transforming maternal or embryonic tissues, which manifests itself as normal growth differences. Heavy metals cause damage and malfunction in the tissues of organisms. Heavy metal toxicity symptoms vary depending on the chemical and can be caused by acute exposure to high amounts or chronic exposure to tiny amounts over time, resulting in cumulative toxicity. The period of exposure is the main cause of heavy metal accumulation in animal tissues. The difference in enzyme concentrations is an indirect indicator of tissue damage. This article describes the clinical features that are useful in the evaluation of heavy metal toxicity and the management options available for heavy metal toxicity in livestock.